Impact of Parkinson's Disease on Complications, Readmission Rates, and Costs of Care following Primary Total Knee Arthroplasty - Marchand, Kevin B.; Vakharia, Rushabh; Sodhi, Nipun; Anis, Hiba; Salem, Hytham S.; Scuderi, Giles R.; Mont, Michael A.; Roche, Martin William (The Journal of Knee Surgery, 2020)
Large-scale studies evaluating the effects of Parkinson's disease (PD) on primary total knee arthroplasty (TKA) are limited. The purpose of this study was to determine if PD patients undergoing primary TKA have increased: (1) medical complications; (2) implant-related complications; (3) readmission rates; and (4) costs. A query was performed using an administrative claims database. The study group consisted of all patients undergoing primary TKA who had a history of PD. Matched non-PD patients undergoing primary TKA served as a control group. The query yielded 72,326 patients (PD = 18,082; matching cohort = 54,244). Pearson's chi-square tests, logistic regression analyses, and Welch's t-tests were used to test for significance between the cohorts. Primary TKA patients who had PD were found to have greater incidences and odds of medical complications (4.21 vs. 1.24%; odds ratio [OR]: 3.50, 95% confidence interval [CI]: 3.15–3.89, p < 0.0001) and implant-related complications (5.09 vs. 3.15%; OR: 1.64, 95% CI: 1.51–1.79, p < 0.0001) compared with the matching cohort. Additionally, the rates and odds of 90-day readmission were higher (16.29 vs. 12.66%; OR:1.34, p < 0.0001) and episodes of care costs were significantly greater ($17,105.43 vs. $15,252.34, p < 0.0001) in patients who had PD. Results demonstrate that PD patients undergoing primary TKA had higher incidences of medical and implant-related complications. They also had increased 90-day readmission rates and costs compared with controls. The findings of this study should be used in risk stratification and should inform physician–patient discussion but should not be arbitrarily used to deny access to care.
Keywords: knee; osteoarthritis; arthroplasty; Parkinson's disease